The use of medical infrared thermography in the detection of tendinopathy: a systematic review. (3rd March 2016) - Chaudhry, Saira; Fernando, Rosemary; Screen, Hazel; Waugh, Charlotte; Tucker, Art; Morrissey, Dylan
Abstract : Background: Tendinopathy is a common sports-related injury. A variety of assessment tools are available but none are diagnostic. We aimed to evaluate the utility of Medical Infrared Thermography (MIT) as a tendinopathy detection tool. Objectives: To guide clinical assessment paradigms by reviewing and critically evaluating the application of MIT for detecting and staging tendinopathy. Methods: PubMed, Web of Science, OVID and Cochrane Library were searched for papers evaluating the use of MIT for tendinopathy detection, published in English from inception to March 2015. Reference lists and citing articles were also searched. Six of 748 studies fulfilled the inclusion criteria and were quality assessed. Results: There is strong evidence for the role of MIT in the detection of chronic lateral elbow epicondylalgia and limited for patellar tendinopathy, with statistically significant side to side temperature differences when comparing injured to non-injured limbs, characterised by the presence of 'hot spots' over a clinically diagnosed tendinopathy. However, MIT of rotator cuff tendinopathy shows no significant difference between injured and non-injured. No work was found on Achilles tendinopathy, plantar fasciitis, gluteal or wrist tendinopathy. Conclusion: The available evidence suggests a role for MIT in the detection of lateral epicondylitis and patellar tendinopathy, however the utility for grading pathology or staging recovery have not been studied in sufficient detail to clarify the relationship between thermographic measurement and severity. There was inconclusive evidence to support the role of MIT in the detection of rotator cuff and various other tendinopathies, and this research is therefore warranted.